#TITLE_ALTERNATIVE# - HANDAYANI PRATIWI (NIM : 12214065), DIAN
The productivity of the reservoir will decrease by increasing the production time of the reservoir. Generally, oil production is done with the help of natural flow energy. If there is a lot of oil saturation lifted to the surface of the reservoir so that before the natural flow of the economy ends or can be in the early life of the reservoir, we can use Enhanced Oil Recovery (EOR) method to improve oil recovery. EOR operations require different surface facilities when compared to surface facilities of natural flow fields. One of the famous EOR methods involved with CO2 in which compressed CO2 is injected to increase the reservoir pressure. CO2 acts like a solvent, and causes oil to expand and flow more easily into production wells. Oil displacement by CO2 injection relies on the phase behavior of gas and oil mixtures, which depend heavily on reservoir temperature, pressure and oil composition. This study presents a comprehensive study of CO2 at Field X that deals with the development of surface facilities used in CO2 injection from oil field and steam power plant with a high CO2 content. In general, the carbon dioxide formed will be maximized by considering certain factors. In this study, a complex CO2 separation operation is developed to produce maximum injection rate of CO2 to the reservoir. Furthermore, CO2 will be injected into EOR well and will be undertaken by subsurface analysis to determine the characteristics of CO2 in the wellbore. This analysis is conducted to determine the condition of CO2 in the wellbore. This is due to the injection into the well is done by the liquid phase of CO2.